2022
DOI: 10.1136/ebmental-2021-300401
|View full text |Cite
|
Sign up to set email alerts
|

Mental healthcare in primary and community-based settings: evidence beyond the WHO Mental Health Gap Action Programme (mhGAP) Intervention Guide

Abstract: ObjectivesThe WHO’s Mental Health Gap Action Programme Intervention Guide (mhGAP-IG) has been widely used in low and middle-income countries. We reviewed literature describing interventions and training programmes beyond the mhGAP-IG, in primary healthcare (PHC) and community-based healthcare (CBH).DesignWe searched studies excluded from our updated mhGAP-IG systematic review, and included in other relevant systematic reviews, for evidence and experience of initiatives integrating mental health into PHC and CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Strong association with AA evidently allowed these individuals to consolidate their behavioural self-efficacy with regard to the control of their alcoholism [12]. In the study by Keynejad, Spagnolo and Thornicroft [15], they confirmed that the findings of the mental health gap action programme intervention guide evidencebased to support the need for research and policy addressing obstacles to the successful combination of mental health into primary health care (PHC) and community-based health settings (CBH), and the need to prioritize neglected disorders, including severe mental illness. An important development in self-help in community mental health centres is the application of group therapy techniques to the situations of mentally challenged individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Strong association with AA evidently allowed these individuals to consolidate their behavioural self-efficacy with regard to the control of their alcoholism [12]. In the study by Keynejad, Spagnolo and Thornicroft [15], they confirmed that the findings of the mental health gap action programme intervention guide evidencebased to support the need for research and policy addressing obstacles to the successful combination of mental health into primary health care (PHC) and community-based health settings (CBH), and the need to prioritize neglected disorders, including severe mental illness. An important development in self-help in community mental health centres is the application of group therapy techniques to the situations of mentally challenged individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Within science, integration from diverse disciplines and building transdisciplinary evidence is critical to address the challenge of promoting neurobehavioral development globally. That researchers have an important responsibility in perinatal mental healthcare and in communicating results concerning perinatal environmental exposure, neurodevelopment, and interventions is emphasized in several fields [15 ▪ ,118,154,193,205,208,230,240–251,257 ▪ ]. Community-oriented participatory research with key stakeholders [252], and community engagement [238] to gather ‘bottom-up’ concerns from parents and practitioners [253] is needed, and may contribute to advocacy [239,253].…”
Section: Global Mental Health and The Promotion Of Neurobehavioral De...mentioning
confidence: 99%
“…8 Lacking data on program implementation within Somaliland specifically, previous research has supported the efficacy of community-based mental health programs in LMICs. 34 This includes studies finding significant reduction in symptoms following group interventions led by members of the community despite an otherwise lack of formal mental health training.…”
Section: Intervention: Islamic Trauma Healingmentioning
confidence: 99%